2019
DOI: 10.32598/ijt.13.3.590.1
|View full text |Cite
|
Sign up to set email alerts
|

The Sub-acute Effect of Lead Exposure on the Auditory Brainstem Response in Male Rats

Abstract: Background: Lead is a major environmental pollutant and can adversely affect humans and animals. There are conflicting data about the ototoxic effect of lead. This study experimentally examined the association between blood lead levels (BLL) and the subsequent hearing impairment in male rats. Methods: Twenty-two male rats were randomly categorized into experimental (exposed to lead acetate, 4 mg/kg by gavage) and control groups. We evaluated the groups by click and tone audiometric burst tests, comparing the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…According to Alimohammadi et al, lead exposure in rats can cause hearing loss [49], but some studies have demonstrated that this does not happen [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…According to Alimohammadi et al, lead exposure in rats can cause hearing loss [49], but some studies have demonstrated that this does not happen [50][51][52].…”
Section: Discussionmentioning
confidence: 99%